Evaluating the Effectiveness of Local Government Revenue Collection Framework: A Study of Choma Municipal Council - Siphiwe Mabhena; Kelvin Chibomba (Journal of Arts, Humanities and Social Science)
The primary aim of this research was to assess the effectiveness of the Local Government Revenue Collection Framework. It was based on several objectives, which included analyzing the process of formulating various types of revenue collection by-laws established by the Choma Municipal Council. Another objective was to determine the degree to which the Choma Municipal Council has enforced these revenue collection by-laws in Choma District. Additionally, the study aimed to identify the challenges associated with enforcing the revenue collection by-laws implemented by the Choma Municipal Council. A case study design was utilized for the research. A sample of 80 respondents was selected using simple random sampling methods. Data was gathered through semi-structured questionnaires and key-informant interviews. The analyzed data was presented using descriptive and inferential statistics with the assistance of Microsoft Word and Excel. The findings indicated that a majority of the respondents were unfamiliar with the concept of revenue collection by-laws. Furthermore, all respondents reported that they had not participated in the formulation process of the revenue collection by-laws prior to their approval at the full council meeting. The study revealed that the Choma district council did not properly follow the procedures for formulating bylaws, resulting in a 30% acceptance rate of revenue collection by-laws. This low acceptance is attributed to public ignorance about the reasons for paying these services. Key challenges identified include a lack of manpower, political influence, inadequate transport, and insufficient public sensitization. Recommendations from the study include incorporating online payment options, engaging the community in local bylaw creation, educating the public on timely levy payments, developing a system to determine appropriate business levies, building infrastructure for small businesses, reducing taxes during the economic recession, and improving customer service training for revenue collectors.